ДЕНЕ ТӘРБИЯСЫ ҲӘМ СПОРТ ПЕНЕН ШУҒЫЛЛАНЫЎ ФОРМАЛАРЫ - Турдымуратов, Ж.А.; Тойлибаев, С.М. (SCIENCE and SOCIETY, 2018)
The article contains information about various forms and types of physical culture and sport in the educational and upbringing activity of the individual.